Education relative à l'environnement, assainissement et sante dans les 1er, 5eme et 9eme arrondissement de Cotonou - AZONHE, THIERRY HERVÉ S. NICÉPHORE; GOZO, Eric; AGBOSSOU, KOSSI EULOGE (My University, 2014)
This study focuses on analyzing the effects of education on environmental sanitation and the health of households in a city of Cotonou. Data were collected on a sample of 318 households (simple random sampling) with information on the sources of information on environmental education, the content of the sessions, people's behavior, the state of health, the environment and the diseases most frequently encountered in the sample. In addition to the descriptive statistics, cross-tabulation was conducted to understand the relationship between the safety and health of the sample households. The results show that the structures responsible for the ERE target all segments of the population. The means of communication used by the structures of radio (9.32 %), television (58%), discussion with friends (20.7%), newspapers (4.3%) and others (7, 68%). Finally, the analysis reveals a strong relation between cases of diarrheas (r=0.6) and the situation of children in the garbage concessions. However, relationships are weak between households claim to respect the recommendations of the ERE and the frequency of certain diseases such as malaria (r=0.2) or diarrhea (r=0.1). However, despite the availability of information, it seemed a mismatch between the information and the state of environmental health (63.29 % of households) which is justified primarily by financial difficulties (71.32 %) or indifference (17.85%) out of the living space is considered a no man's land. The epidemiological context is typical of such environments with diseases such as diarrhea in children under 05 years (69.83 %) and dermatitis (23.81 %). Reducing the economic cost of these diseases through strengthening education on the environment.
Keywords: Cotonou on Environmental Education; Unsafe; Diseases